INSIGHTS INTO DIAGNOSIS AND MANAGEMENT OF ADVANCED MULTIPLE MYELOMA - Vasile Musteata (Elsevier, 2021)
Objective: The advanced stages of multiple myeloma (MM) commonly manifest a recurrent evolution, unfavorable prognosis and negative socio-economic impact. The increased rates of morbidity and DALYs, frequent complications and relapses, unfavorable socio-economic impact characterize MM as an actual issue of hematology and public health. The objective of the study was the identification of diagnostic patterns and the evaluation of short- and long-term results of treatment of the advanced stages of MM. Methodology: The study is a cross-sectional descriptive analysis of a cohort of 50 newly diagnosed patients with advanced stages of MM, who have been treated and followed-up at the Hematology Dept. of the Oncology Institute from Moldova during 2016-2020. The diagnosis was assessed by cytological, immunohistochemical examinations of the bone tissue and bone marrow, and ELISA immunological test of the peripheral blood. The stage was asserted in each case according to the Revised International Staging System. Results: The patients age ranged between 28-75 years (median - 57.7 years). MM developed mainly in persons aged 60-69 (52%) years and in rare cases under 39 years (6%). Females were 29 (58%), and males - 21 (42%). 31 (62%) patients were diagnosed in stage III, 14 (28%) - in stage II and  5 (10%) - in stage I. Immunoglobulin (Ig) G isotype was detected in 28 (56%) cases, IgA - in 12 (24%), light chains (Bence Jones MM)  - in 10 (20%). Very good partial responses were achieved in 25 (50%) of patients. Conclusion: MM was diagnosed mostly in patients of 60-69 years, females and stage III disease. Bone marrow myeloma cells ranged between 30-67% (median - 46%). Concerning the Ig isotype distribution in MM, IgG accounted the majority of cases. Refractory chronic renal failure was the most common complication (50% of cases) in advanced MM. Targeted chemotherapy proved to be efficient in the advanced stages of MM regardless of the gender, age  and disease span. Very good partial responses lasted 12-24 months.